Pemakaian Obat Nefrotoksik Sebagai Determinan Drug-Induced Acute Kidney Injury (D-AKI) - Hadiwati, Rangkay; Andrajati, Retnosari; Syafhan, Nadia Farhanah; Wahono, Dwi Edi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Events related to drug reactions are very difficult to recognize, because they often look like other diseases and many symptoms of drug reactions appear, especially for short drug exposures. Acute Kidney Injury is a condition that affects the structure and function of the kidneys, which is characterized by a sudden decrease in kidney function which causes necrosis of the tubules. The aim of this study was to analyze the prevalence of Drug-Induced Acute Kidney Injury and determine the main risk factors as well as drug data that can influence the increase in serum creatinine levels during treatment. This study implemented a cross-sectional design. The sampling location was the Medical Records section of Gatot Soebroto Army Hospital, with a sample size of 56 patients identified using the Kidney Disease Improving Global Outcomes (KDIGO) criteria and using trigger tools. Data were analyzed using the Chi-square test. The results of the analysis showed that the prevalence of Drug-Induced Acute Kidney Injury in the RSPAD Gatot Soebroto inpatient room was 8.975%-18.527%. Factors that influence the occurrence of Drug-Induced Acute Kidney Injury in the inpatient room were comorbidities (PR = 8.975; 95% CI = 1.317-61.159; p-value = 0.025) and drug interactions (PR = 18.527; 95% CI = 1.727 -177.909; p-value = 0.011). In general, the most widely used nephrotoxic drugs were a combination of >3 types of nephrotoxic drugs, diuretics, NSAIDs, cephalosporins, ARBs, ACEi and chemotherapy drugs. Based on the research results, it was concluded that the use of nephrotoxic drugs was a determinant of Drug-Induced Acute Kidney Injury in the Gatot Soebroto Army Hospital inpatient room.Keywords: kidney disease; Drug-Induced Acute Kidney Injury; nephrotoxic drugs; trigger tools; creatinine ABSTRAK Kejadian yang berhubungan dengan reaksi obat sangat sulit dikenali, karena sering tampak seperti penyakit lain dan banyak gejala reaksi obat yang muncul, terutama untuk paparan obat yang singkat. Acute Kidney Injury adalah salah satu dari kondisi yang mempengaruhi struktur dan fungsi ginjal, yang ditandai dengan penurunan fungsi ginjal secara tiba-tiba yang menyebabkan nekrosis pada tubulus. Tujuan penelitian ini adalah menganalisis prevalensi Drug-Induced Acute Kidney Injury dan menentukan faktor risiko utama serta data obat-obatan yang dapat mempengaruhi peningkatan kadar kreatinin serum selama dirawat. Penelitian ini menerapkan desain cross-sectional. Tempat pengambilan sampel adalah bagian Rekam Medis RSPAD Gatot Soebroto, dengan ukuran sampel adalah 56 pasien yang diidentifikasi dengan menggunakan kriteria Kidney Disease Improving Global Outcomes (KDIGO) dan menggunakan trigger tools. Data dianalisis menggunakan uji Chi-square. Hasil analisis menunjukkan bahwa prevalensi Drug-Induced Acute Kidney Injury di ruang rawat inap RSPAD Gatot Soebroto adalah 8,975%-18,527%. Faktor-faktor yang mempengaruhi terjadinya Drug-Induced Acute Kidney Injury di ruang rawat inap adalah komorbid (PR = 8,975; 95% CI = 1,317-61,159; p-value = 0,025) dan interaksi obat (PR = 18,527; 95% CI = 1,727-177,909; p-value = 0,011). Secara umum obat nefrotoksik yang paling banyak digunakan adalah kombinasi obat nefrotoksik >3 macam, obat diuretik, NSAID, sefalosporin, ARB, ACEi dan obat kemoterapi. Berdasarkan hasil penelitian disimpulkan bahwa pemakaian obat nefrotoksik merupakan determinan dari Drug-Induced Acute Kidney Injury di ruang rawat inap RSPAD Gatot Soebroto.Kata kunci: kidney disease;  Drug-Induced Acute Kidney Injury; obat nefrotoksik; trigger tool; kreatinin